Construction of an endgame rulebook for Sylver Coinage using trees of numerical semigroups - Bras-Amorós, Maria; Moskowitz, Gilad; Ponomarenko, Vadim (Communications in algebra, 2025)
In this paper we show how the algorithms to explore the tree of numerical semigroups can be used to calculate the winningness of positions in the game of Sylver Coinage. We introduce a new invariant for numerical semigroups, the minimal distance, and show how it can be used to prune the tree of numerical semigroups for an efficient way of calculating the winningness of positions in the game of Sylver Coinage. We end with a few open questions that were spawned as a result of this research.